ANALISIS KENDALA, SOLUSI DAN FAKTOR DETERMINAN GURU DALAM IMPLEMENTASI PEMBELAJARAN KURIKULUM MERDEKA TERINTEGRASIKAN PEMBELAJARAN MENDALAM DI SEKOLAH DASAR - Hafsyah Auliyaa H; Rina Depi Yanti; Arif Jati Kusuma Suwandi; Uut Aprilah Pangestu M; Taufik Muhtarom (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the obstacles faced by elementary school teachers in implementing the Merdeka Curriculum integrated with deep learning, identify recommended solutions to overcome these obstacles, and examine the determinant factors influencing its successful implementation. This study employed a Systematic Literature Review (SLR) method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were collected through a search of scientific articles indexed in Google Scholar, ERIC, and GARUDA published between 2020 and 2026. The identification process yielded 38 articles. After a screening process based on predetermined inclusion and exclusion criteria, 20 articles met the eligibility requirements and were selected as data sources. The data were analyzed using thematic analysis. The findings indicate that the implementation of the Merdeka Curriculum integrated with deep learning still faces several challenges, particularly teachers’ limited understanding of deep learning concepts, inadequate facilities and infrastructure, difficulties in designing meaningful learning experiences, and low levels of digital literacy. Recommended solutions include continuous teacher training and mentoring, strengthening professional learning communities, optimizing the use of educational technology, and fostering a collaborative school culture. The determinant factors influencing successful implementation include teachers’ professional competence, school leadership support, the availability of learning facilities, sustainable professional development, and digital literacy. The findings suggest that successful implementation requires strong synergy among teachers, schools, and educational policymakers.